2015
DOI: 10.1080/00071668.2015.1059407
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid and nitric oxide interaction mediates food intake in neonatal chicken

Abstract: The aim of the current study was to investigate the interaction of the nitric oxide and cannabinoidergic systems on feeding behaviour in neonatal chicken. A total of 6 experiments were designed to evaluate the interaction between cannabinoidergic and nitrergic systems on food intake in 3-h food-deprived (FD3) neonatal chickens. In Experiment 1, chickens received intracerebroventricular (ICV) injections of saline, 2-arachidonoylglycerol (2-AG) (a CB1 receptor agonist, 2 µg), l-arginine (nitric oxide precursor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…To the best of our knowledge, there are no studies describing the interaction between CBergic and GABAergic systems on food intake in FD 3 neonatal layer-type chickens. According to the results, ICV injection of CB 1 and CB 2 agonists amplified food consumption in layertype chicks which was similar to mammals (Chen et al, 2006;Wiley et al, 2012) and recent studies on layertype chicks (Alizadeh et al, 2015;Hassanpour et al, 2015). However, these results were dissimilar compared to broilers which only CB 2 receptors were responsible for feeding (Emadi et al, 2011;Novoseletsky et al, 2011).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…To the best of our knowledge, there are no studies describing the interaction between CBergic and GABAergic systems on food intake in FD 3 neonatal layer-type chickens. According to the results, ICV injection of CB 1 and CB 2 agonists amplified food consumption in layertype chicks which was similar to mammals (Chen et al, 2006;Wiley et al, 2012) and recent studies on layertype chicks (Alizadeh et al, 2015;Hassanpour et al, 2015). However, these results were dissimilar compared to broilers which only CB 2 receptors were responsible for feeding (Emadi et al, 2011;Novoseletsky et al, 2011).…”
Section: Discussionmentioning
confidence: 60%
“…Reports claim just CB 1 receptors have a regulatory role on appetite in broilers Novoseletsky et al, 2011). Recent reports revealed both CB 1 and CB 2 receptors have hyperphagic effect in neonatal layer-type chicken (Alizadeh et al, 2015;Hassanpour et al, 2015).…”
Section: Involvement Of Gaba and Cannabinoid Receptors In Central Foomentioning
confidence: 99%
See 2 more Smart Citations
“…Intracerebroventricular (ICV) injection of Nω-Nitro-l-arginine methyl ester (L-NAME), NOS inhibitor, decreased food intake in rats (De Luca et al 1995) and avian species (Choi et al 1994) and NO is recognized as an orexigenic molecule. On the other hand, some studies in neonatal chicks showed contrary results and L-NAME stimulated food intake (Alimohammadi et al 2015;Hassanpour et al 2015) and NO Abstract Most physiological behaviors such as food intake are controlled by the hypothalamus and its nuclei. It has been demonstrated that injection of the paraventricular nucleus of the hypothalamus with nitric oxide (NO) donors elicited changes in the concentration of some amino acids, including GABA.…”
Section: Introductionmentioning
confidence: 98%